Meningkatkan Kemampuan Menyelesaikan Soal Cerita Pada Muatan Matematika Melalui Model Pembelajaran Problem Based Learning Berbantuan Media Konkret Pada Siswa Kelas III B di Sekolah Dasar - Rohani, Anti; Yantoro, Yantoro; Sholeh, Muhammad (Peneliti.net, 2024)
The purpose of this study was to describe how to improve the ability of class III B students in solving math word problems in elementary schools using the Problem Based Learning model assisted by concrete media. This classroom action research was carried out in 2 cycles, each cycle consisting of 2 meetings and there were 4 stages namely planning, implementation, observation and reflection. The data collection is by observation, test and documentation. The data analysis techniques are qualitative and quantitative. The results of this study indicate that the application of the Problem Based Learning model assisted by concrete media can improve the ability of class III B students in solving math word problems. The results obtained from the pre-cycle were 17.39%, in the first cycle it was 62.96% and in the second cycle it was 76.92%. Then it can be concluded that the application of the Problem Based Learning learning model assisted by concrete media can improve the ability of class III B students in solving word problems on math content.